#Interpersonal Competence, Loneliness, Fear of Negative Evaluation, and Reward and Punishment as Predictors of Social Media Addiction and Their Accuracy in Classifying Adolescent Social Media Users and Non-Users - Savci, Mustafa; Aysan, Ferda (Turkish Green Crescent Soc, 2018)
This research investigates whether or not interpersonal competence, loneliness, fear of negative evaluation, and reward and punishment predict social media addiction and the level of accuracy at which adolescent social media users and non-users are classified. For this general purpose, the research examines these variables' impact on social media addiction in the first stage. The second stage examines the accuracy with which these variables classify adolescent social-media users and non-users. The first phase of the research has been performed over 282 adolescents (123 girls and 159 boys) who have at least one social media account and have used social media for the last year. The second stage of the research has been conducted over 144 adolescent social media non-users (64 girls and 80 boys) in addition to the 282 adolescents from the first phase. Data from the study has been collected using the Social Media Disorder Scale, Interpersonal Competence Scale, Social Anxiety for Adolescents Scale, UCLA Loneliness Scale-Short Form, Behavioral Inhibition System/Behavioral Activation System Scales, and a personal information form. According to the results from the first phase of the research, interpersonal competence, loneliness, fear of negative evaluation, and reward and punishment are found to predict social media addiction at a meaningful level. According to the results from the second phase of the research, interpersonal competence, loneliness, fear of negative evaluation, and reward and punishment correctly classified 74% of adolescent social media users and non-users. These results show interpersonal competence, loneliness, fear of negative evaluation, and reward and punishment to affect social media addiction and social media use/non-use.
Keywords: Social media addiction; Interpersonal competence; Loneliness; Fear of being negatively evaluated; Reward; Punishment